THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON THE PERFORMANCE OF MAKASSAR CITY EDUCATION OFFICE EMPLOYEES - Elsi Mayori; Muhammad Ichwan Musa; Uhud Darmawan Natsir; Romansyah Sahabuddin; Abdi Akbar (Transpublika Publisher, 2023)
Leadership style and work discipline are recognized as pivotal elements that shape the behaviors, attitudes, and outcomes of employees within an organization. Leadership style pertains to the approach adopted by leaders to guide, motivate, and manage their subordinates, while work discipline involves the adherence to established rules, regulations, and norms within the workplace. This study aimed to investigate the impact of leadership style and work discipline on the performance of employees within the Makassar City Education Office. The research comprised a total of 94 employees from this office. Employing a quantitative research approach, the study involved quantitative analysis to evaluate the research hypothesis, utilizing IBM SPSS version 25 software. The findings revealed a positive and substantial influence of both leadership style and work discipline on employee performance. This conclusion was drawn from a t-statistic value of -2.655, which was less than the t-table value (1.66177), and a significance value of 0.000, indicating statistical significance (p < 0.05). The outcomes also demonstrated the significant impact of work discipline and leadership style on employee performance, with a calculated F-value of 25.215, surpassing the threshold of 3.10, and a significance value of 0.000, further confirming the significance of the findings (p < 0.05).